(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
Five species of birds were recorded for the fist time in Malpelo Island. With this information, the total number of birds recorded in the island ascends to 65 species. The new bird records are Upland Sandpiper, Semipalmated Sandpiper, Surfbird, Great Crested Flycatcher and the Northern Waterthrush.